Penataan ulang trigliserida minyak saga utan (Adenanthera pavonina) melalui trans-esterifikasi - Ramses J Napitupulu; Tatang H Soerawidjaja (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2008)
The triglyseride re-arrangement of the forest sunflower oil in order to develop new forest sunflower oil with different properties has been done in this research. The re-arrangement has been done by some steps of process such as extraction step, tranesterification step, fractionation step, and continued by directed interesterication reaction. The re arrangement happen in directed interesterification reaction at 54°C assisted by natrium hydrokside anhydrate catalyst. This treatment is aimed to maintain the equilibrium in the reacting mixture to be kept directed to the preferred product development (metil fignoserat) and then it can be separated from the reacting mixture. The forest sunflower oil has acid number of 0,841 mg KOH/gr oil, soap number 182,73 mg KOH/gr oil, and iod number 93,28 gr iod/100 gr oil. After the re-arrangement process then two kind of product of new forest sunflower oil has been obtained. Ones with the soap number of 185,94 mg KOH/gr oil, and the other contain metil lignoserat solid with soap number of 152,23 mg KOH/gr oil. From the whole process steps, it was obtained the new forest sunflower oil that has rich unsaturated fatty acids content like oleat acid (omega 9) and finoleat acid (omega 6).Keywords: Acid Number, Inter-esterification, Iodine Number, Re-arangement, Soap Number, Triglyseride Abstrak Dalam penelitian ini dilakukan penataan ulang trigliserida minyak saga utan, sehingga minyak saga utan baru memifiki sifat-sifat fisik yang berbeda dari minyak saga utan awal. Penataan ulang minyak saga utan dilakukan melalui beberapa tahap yaitu tahap ekstraksi, reaksi transesterifikasi, fraksionasi, dan dilanjutkan dengan reaksi interesterifikasi terarah. Penataan ulang terjadi pada reaksi interesterifikasi terarah pada temperatur 54°C dengan bantuan katafis natrium hidroksida anhidrat. Hal ini dimaksudkan agar kesetimbangan di dalam campuran reaksi terus menerus bergeser ke arah pembentukan produk yang dikehendaki (metil lignoserat) tersingkir dari campuran reaksi. Minyak saga utan memiliki angka asam 0,841 mg KOH/gr minyak, angka penyabunan 182,73 mg KOH/gr minyak, dan angka iodium 93,28 gr iod/100 gr minyak. Setelah dilakaukan proses penataan ulang maka didapatkan dua buah produk yaitu minyak saga utan baru dengan angka penyabunan 185,94 mg KOH/gr minyak, dan padatan metil fignoserat dengan angka penyabunan 152,23 mg KOH/gr minyak. Dari tahapan proses, didapatkan minyak saga utan baru yang kaya akan kandungan asam lemak tak jenuh seperti asam oleat (omega 9) dan asam finoleat (omega 6). Kata kunci: Angka Asam, Angka Iodium, Angka Penyabunan, Interesterifikasi, Penataan Ulang, Trigliserida